Impact of sidedness of colorectal cancer on tumor immunity - Takasu, Chie (PLoS One, 2020)
BACKGROUND: Clinical and molecular characteristics differ between right-sided and left-sided colorectal cancer (CRC). This study aimed to clarify the correlation between CRC sidedness and tumor immunity. METHODS: A total of 102 patients who underwent curative colectomy for stage II/III CRC were included in this study. The expression of programmed cell death (PD)-1, PD1-ligand 1 (PD-L1), forkhead box P3 (Foxp3), transforming growth factor (TGF)-β, and indoleamine-pyrrole 2,3-dioxygenase (IDO) were examined using immunohistochemistry and the relationships between sidedness and several prognostic factors were examined. RESULTS: Clinicopathological factors were not significantly different between right- and left-sided CRC. The tumor immunity-related molecule PD-L1 was more highly expressed in right-sided than in left-sided CRC (62.9% vs. 30.6%, p<0.01). No significant difference was found in overall survival (OS) and disease-free survival (DFS) by sidedness. PD-1 and Foxp3 expression were significant prognostic factors for OS. Lymph node metastasis (N), lymphatic invasion (ly), and PD-L1 expression were significant prognostic factors for DFS. In right-sided CRC, IDO-positive patients had a poor OS (p<0.05), and IDO was the only independent prognostic indicator for OS. N and venous invasion were identified as independent prognostic indicators for DFS. In left-sided CRC, univariate analysis identified PD-1, PD-L1, and Foxp3 expression as significant predictors of poor OS. Multivariate analysis confirmed PD-L1 expression as an independent prognostic indicator. N, ly, and PD-L1 expression levels were identified as significant predictors of poor DFS. CONCLUSIONS: The prognostic factors were IDO in right-sided CRC and PD-L1 and Foxp3 in left-sided CRC. These findings indicated that tumor immunity might play different roles depending upon sidedness. Tumor location may be an important factor to consider when assessing immune response and therapeutic decisions in CRC patients.